Prevalence and Pattern of Birth Defects in Saudi Arabia: A Systematic Review of Observational Studies - Ebtihal Elameen Eltyeb; Majidah Hussain Asiri Halawi; Thekra Badr Mohammed Tashari; Khaled Alharbi; Ohoud Saad Alsayari; Danah Abdullah Albarrak; Raga Abdelkhalig Eltayeb; Ali Ali Ahmed Al-Makramani; Isameldin Elamin M. Medani (MDPI AG, 2023)
Introduction: Birth defects are a significant concern since they can lead to permanent disability and death. This study comprehensively reviews the prevalence and patterns of birth defects in Saudi Arabia. Methods: A systematic analysis of the literature retrieved from three databases (Pub Med, Science Direct, and the Saudi digital library) published between 1989 and 2022 was performed. Observational studies that addressed the prevalence and patterns of birth defects in Saudi Arabia were chosen based on the eligibility criteria, while systematic reviews, review articles, non-relevant articles, and studies that did not fulfill the eligibility criteria were excluded. Quality and risk of bias were evaluated based on the JBI and GRADE tools, respectively. Results: We identified 26 eligible publications of 1277 records that included 297,668 patients from different regions of Saudi Arabia. The highest overall prevalence of birth defects was 46.5 per 1000 live births compared to a lowest rate of 8.6 per 1000 in one study. Several studies have reported positive associations of consanguinity, maternal folic acid supplementation, family history of birth defects or genetic abnormalities, and maternal co-morbidities. The most frequent birth defects include cardiac, genitourinary, craniofacial, and nervous system defects. Conclusion: Robust findings have improved our understanding of the prevalence and pattern of birth defects in Saudi Arabia. Importantly, future studies will likely require multicenter collaboration to arrive at appropriate sample sizes in the context of the effects of risk factors on elevated prevalence. Furthermore, quantitative data require careful evaluation in more complex statistical models.